2018
DOI: 10.1002/acm2.12388
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of potential errors during patient treatment planning

Abstract: PurposeData errors caught late in treatment planning require time to correct, resulting in delays up to 1 week. In this work, we identify causes of data errors in treatment planning and develop a software tool that detects them early in the planning workflow.MethodsTwo categories of errors were studied: data transfer errors and TPS errors. Using root cause analysis, the causes of these errors were determined. This information was incorporated into a software tool which uses ODBC‐SQL service to access TPS's Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Although automation in the context of treatment planning can involve many different steps, such as QA issues 55,56 or plan review, 57 it mainly consists of two distinct parts; volume delineation (or segmentation) and planning related issues. In the following, we give a short review of these items with emphasis on the specific issues relevant for PT.…”
Section: Automation In Proton Treatment Planningmentioning
confidence: 99%
“…Although automation in the context of treatment planning can involve many different steps, such as QA issues 55,56 or plan review, 57 it mainly consists of two distinct parts; volume delineation (or segmentation) and planning related issues. In the following, we give a short review of these items with emphasis on the specific issues relevant for PT.…”
Section: Automation In Proton Treatment Planningmentioning
confidence: 99%
“…One example is a study by Luk et al 31 who, using a Bayesian network‐based radiotherapy plan verification model, suggested a 4‐year training dataset to optimize the performance of the network, and yearly updates were considered sufficient to capture the evolution of clinical practice and maintain fidelity. Other recently published papers describe and quantify time savings and error reduction using different analyses 21,32–34 . A review of these new techniques and publications is instructive in looking at the future of initial chart check automation.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the increasing reliance on initial chart check automation, TG-275 provides an estimation of the types of checks that might be automated in the future, based on a review of prior publications up to 2016 [8][9][10][11][12][13][14][15][16][17][18][19] and other considerations. The feasibility of automation as indicated in TG-275, however, may be increasing with the rapid development of techniques in locally developed programs, 20,21 vendor solutions, and recent acceleration of machine learning efforts. [22][23][24][25][26][27][28][29][30] Some items previously deemed impossible for automation may become feasible through the development of new and easy-to-implement machine learning techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue of developing improved methods of error detection, we proposed a novel artificial intelligence (AI) approach using Bayesian networks (BN). This approach was taken because although automated rules-based approaches have been developed to assist the plan checking process [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and have led to reduced error rates and increased efficiency, 22 it was felt that they have significant limitations and do not provide the sort of domain knowledge and human reasoning, which is essential to a comprehensive review of treatment plans.…”
Section: Introductionmentioning
confidence: 99%